Financing Strategy for FSRU Belawan Project: a Recommendation on Financing Strategy for the FSRU Belawan Project - Sentosa, Erik; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2012)
Related to PGN’s plan to invest in Floating Storage and Regasification Unit (FSRU) in Belawan, Medan, Budget Division of PGN needs an efficient financing strategy. Based on PGN’s financial condition in 2010, four scenario of financing strategy were analyzed. The four financing strategy are carried out by issuing right, issuing corporate bond, combination of issuing right and utilizing company’s liquid assets, and combination between issuing corporate bond and utilizing company’s liquid asset. Each scenario is analyzed by computing its WACC and assessing NPV, IRR and payback period based on the calculated WACC. Along with that, the opportunity costs, securities issuance costs, and its effect to company’s liquidity are also assessed. The recommended solution is to issue corporate bond and utilizing excess liquidity, since this strategy has the highest NPV, no opportunity cost in issuing undervalued stock, short period of debt repayment, and relatively acceptable effect on company liquidity. Another part of the report is the risk management strategy for the project. The risk management is mainly mitigating the funding liquidity risk, and the market risk of interest rate, foreign currency and natural gas price. The implementation plan will discuss about the project management in corporate bond issuance and liquidity allocation for project financingand risk management.   Keywords: Financing strategy, FSRU, Right issue, Corporate bond issue, WACC.